Benign Partial Epilepsy in Infancy - J Gordon Millichap (Pediatric Neurology Briefs)
The frequency of occurrence of benign partial epilepsy in infancy (BPEI) in a first line general hospital was determined among 75 patients presenting with epilepsy in the first 2 years of age and evaluated between 1987 and 1993 at the Departments of Paediatrics, Anjo Kosei Hospital, Anjo Aichi, and Nagoya University School of Medicine, Nagoya, Japan.